Mapping of tourism products in Perak Tengah districts using geographic information systems / Fatin Nabilah Omar, Norainah Abdul Rahman and Kamariah Abdullah - Omar, Fatin Nabilah; Abdul Rahman, Norainah; Abdullah, Kamariah (Universiti Teknologi MARA, Perak, 2023)
Perak Tengah District had been excluded from being promoted as rural tourism in Perak main tourism clusters. The main problem is the tourism resources have not yet been effectively publicised and utilised and there is no official digital tourism database of tourism products in Perak Tengah District. The aim of this paper is to capture all potential tourism products in Perak Tengah and present it in the interactive map. In this paper, a software QGIS and Google Earth are used to locate and map the distribution of tourism in Perak Tengah District. According to the findings, 229 different tourism products have been located within the study area. The findings show, inadequacy of trade and service and accommodation to support tourism development. Besides that, these tourism products areas are supported by signages, roads, accessibility, parking, and facilities that are sufficient and satisfactory conditions for tourists to come. The mapping of tourism products is categorised into five including place of attraction, food and beverages, accommodation, education, trade, and services. By using coordinates made up of graphic data and qualities for each identified tourist attraction, the results of the identification of the distribution of tourism products are projected on a map.